Assessing Self-Regulation as a Cyclical, Context-Specific Phenomenon: Overview and Analysis of SRL Microanalytic Protocols. (20th June 2012) - Cleary, Timothy J.; Callan, Gregory L.; Zimmerman, Barry J.
Abstract : The primary purpose of this paper is to review relevant research related to the use of an assessment technique, called Self-Regulated Learning (SRL) Microanalysis. This structured interview is grounded in social-cognitive theory and research and thus seeks to evaluate students' regulatory processes as they engage in well-defined academic or nonacademic tasks and activities. We illustrate the essential features of this contextualized assessment approach and detail a simple five-step process that researchers can use to apply this approach to their work. Example questions and administration procedures for five key self-regulation subprocesses (i.e., including goal-setting, strategic planning, monitoring, self-evaluation, and attributions) are highlighted, with particular emphasis placed on causal attributions. The psychometric properties of SRL microanalytic assessment protocols and potential areas of future research are presented.